Keterampilan Membuka Dan Menutup Pelajaran Yang Efektif Dalam Konteks Pendidikan Islam Di Madrasah Aliyah Swasta Amaliyah Sunggal - Harahap, Muhammad Yunan; Ependi, Rustam; Syahrial Harahap, Abdi; Ikhsan, Fadli Nurul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research explores effective opening and closing skills in the context of Islamic Religious Education at Madrasah Aliyah Swasta Amaliyah Sunggal. The method used in this research is qualitative while data collection through observation, interview and document study. The purpose of this study was to explore the skills of opening and closing an effective lesson at the private madrasah aliyah Amaliyah Sunggal. The results showed that opening the lesson involved the use of prayer, brief motivation, and linking the material to real life, while effective closing included summarizing the material, reflection, and prayer. The study also found that the use of inspirational stories and reflective questions significantly increased students' curiosity and activeness in learning. The use of varied and innovative learning methods, including information technology and interactive learning media, is key in improving the quality and effectiveness of learning. The challenges teachers face in implementing these skills include variations in learning methods, student understanding and awareness, integration of Islamic values, and limited resources.